SDoT-NFV: A Distributed SDN Based Security System with IoT for Smart City Environments (GUB Journal of Science and Engineering, 2021)
The Internet of Things (IoT) is a key developing innovation aimed at linking objects via the Internet. While, Software Defined Networking (SDN) is another modern network- ing domain intelligence innovation that increases network effi- ciency and enhances security, reliability, and protection through dynamic software programs. In this paper, we proposed a distributed secure SDoT-NFV architecture for smart cities with Network Function Virtualization (NFV) implementation. We integrated highly protected SDN that delivers better network ef- ficiency, protection, and privacy results. It also secures metadata within each layer as well as payload. In addition, this architecture attempted to implement a more efficient method for constructing a cluster via SDN. Moreover, SDN-IoT with the NFV ideas brings benefits in terms of energy conservation and load balancing to the relevant fields. In addition, several distributed controllers have suggested enhancing accessibility, integrity, anonymity, con- fidentiality, and so on. We also implemented an energy-efficient Cluster Head Selection (CHS) algorithm to make use of our proposed architecture. The network offers greater protection of each network layer as opposed to the traditional network in the proposed architecture. Lastly, we analyze the efficiency of the proposed architecture with different network parameters (throughput, RTT, and Time sequence) for smart cities.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 7, Dec 2020 P 27-35